A Defensoria Pública como instrumento de efetivação dos direitos fundamentais: o acesso à informação sobre o divórcio e a dissolução da união estável e suas consequências para a infância e a juventude - Carneiro, Téssia Gomes (Universidade Federal do Tocantins, 2016)
This Technical Report results from elaborate study whose aim justifies making the attached manual. It is designed to guide the defender assistants (information desk and screening employees), the trainees and the legal analysts (workers graduated in Law that assists the public defenders). It is also about the procedures and useful information to families that experience the divorce or dissolution of stable union, as well as about the consequences for children and adolescents, considering the principle of absolute priority. It also brings the figure of conciliation as a means of treating consensually conflicts in the family sphere to allow communication between former spouses through intervention of the figure of the conciliator, who, besides clarifying questions relating to division of property, custody and visits to children, favors amicable settlement